Taxonomic guide and historical review of echinoids (Echinodermata: Echinoidea) from northeastern Brazil - Gondim, Anne Isabelley; de Moura, Rafael Bendayan; Christoffersen, Martin Lindsey; Dias, Thelma Lúcia Pereira (Zootaxa, 2018)
The class Echinoidea contains among the best-known echinoderms. The group has left the most complete fossil record of this phylum, and contains about 1000 living species, of which 51 are recorded along the Brazilian coast. Although the first record of echinoids in Brazil was made 369 years ago, the knowledge of this fauna remains quite unsatisfactory from a taxonomic and ecological point of view, particularly in the north and northeastern regions of the country. This study provides the first annotated list of echinoids from northeastern Brazil. The studied material largely belongs to collections of the Federal University of Paraíba (CIPY), Federal University of Sergipe (LABIMAR-UFS), Federal University of Bahia (MZUFBA), University of São Paulo (MZUSP), and National Museum of the Federal University of Rio de Janeiro (MNRJ). Thirty-two species from 29 genera, 18 families, and 10 orders were identified. Descriptions of species are provided. Highest diversities of Echinoidea were encountered for the states of Bahia (19 spp.), Alagoas (11 spp.), Paraíba (10 spp.), Ceará (7 spp.), Rio Grande do Norte (7 spp.), and Pernambuco (6 spp.). On the basis of the data analysed, Maranhão (2 spp.), Piauí (2 spp.), and Sergipe (3 spp.) have the lowest diversity. Sandy substrates and depths below 10 m were the least sampled areas over the continental shelf. Although the studied species are common, some taxonomic problems were encountered and discussed. We also provide ecological information and comments on status of the species from the studied region. As a result of this inventory, we were able to provide the first assessment of the echinoid fauna of northeastern Brazil.